1998
DOI: 10.4141/a97-049
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting kid survival in five goat breeds

Abstract: Data on 7757 kid's records (2424 Alpine, 1417 Granadina, 2225 Nubian, 1043 Saanen and 648 Toggenburg) were used to study the effect of the breed, sex, litter size, birth weight, dam age, year of birth and birth period (October–January, February, March, April–July) on kid survival rates from 0–15, 16–90 and 91–210 days of age. Survival of kids was in general highest in Granadina and lowest in Toggenburg, while values in the other breeds, tended to be intermediate. Survival in males was lower than in female kids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 8 publications
2
4
1
1
Order By: Relevance
“…There was no significant difference in survival rate between ram and doe kids (84.0 ± 0.89 vs. 84.9 ± 0.89). This is in contrast with the findings of Perez-Razo et al (1998). Pre-weaning survival rates for kids in the different studs are presented in Table 2.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…There was no significant difference in survival rate between ram and doe kids (84.0 ± 0.89 vs. 84.9 ± 0.89). This is in contrast with the findings of Perez-Razo et al (1998). Pre-weaning survival rates for kids in the different studs are presented in Table 2.…”
Section: Resultscontrasting
confidence: 54%
“…Very little work on mortality rate in goats, especially Angora goats, has been published to date (Van der Westhuizen, 1980;Terblanché, 1988;Husain et al, 1995;Geyer, 1998;Perez-Razo et al, 1998;Awemu et al, 1999, Turkson, 2003. These authors cited losses of 10 to 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Survival rates were greater (P = 0.025) for March-born vs. May-born kids, decreased with increasing htter size, and were less (P < 0,01) in aged does (Table 3), Sex of kid did not affect kid survival rates. The current literature is inconsistent in defining the impact of nongenetic factors on goat kid survival to weaning (Erasmus et al, 1985;Gebrelul et al, 1994;Husain et al, 1995;Pérez-Razo et al, 1998;Alexandre et al, 1999;Marai et al, 2002). Three of 4 studies found month (or season) of birth to be important, 3 of 5 indicated sex of kid was significant, 3 of 5 reported age (or parity) of doe to be important, and 2 of 6 indicated litter size significantly affected kid survival to weaning.…”
Section: Preweaning Kid Survivalmentioning
confidence: 92%
“…143% of kids born in Rendang District increased the efficiency of goat production. The results of this study were in agreements with Perez-Razo et al (1998) who reported that high survival rate of kids reared in Rendang District minimized the cost of rearing as it resulted in more productive goats and thus provided more profit to the households as more kids and goats sold. Maintaining good kid rearing management hence high survival rates of newly born kids could be one of the development strategies that will help in improving goat production in Rendang District.…”
Section: Goats and Their Profilessupporting
confidence: 89%
“…Litter size was one aspect of maternal abilities affecting birth weight and was used as an indicator to measure the reproductive performance of goats. Published data on litter size that was reported from 0.99 to 2.34 in different genotypes of does with information about the type of birth, sex of kid, and parity of does under different ecological and management conditions is summarized in (1996) In prolific species, the high level of competition between foetuses had a meaningful effect on developmental capacity, survival rate of the foetus and individual growth rate of the animals born in the litter and during the preweaning period (Nowak 1996;Perez-Razo et al 1998;Mellado et al 2000a;Nowak et al 2000;Simsek & Bayraktar 2006;Simsek et al 2007;Mahmilia & Elieser 2008). In other words, higher litter size was correlated with lower birth weight and higher losses of young in goats during the first few days of life (Ruvuna et al 1991;Menendez-Buxadera et al 2003;Menendez-Buxadera et al 2004).…”
Section: Litter Sizementioning
confidence: 99%